Petroleum Development and Environmental Conflict in Aotearoa New Zealand : Texas of the South Pacific. - Loomis, Terrence M. (Lexington Books, 2016)
Petroleum Development and Environmental Conflict in Aotearoa New Zealand: Texas of the South Pacific examines the circumstances under which environmental opposition to state policies to promote oil and gas development has led to far-reaching changes in institutional relations between the state and civil society.